The effect of related party transactions on firm performance: The moderating role of political connection in Indonesian banking - Supatmi; Sutrisno T.; Erwin Saraswati; Bambang Purnomosidhi (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This study aims to examine the effect of related party transactions (RPTs) on banks' performance and investigates political connections as moderator in their causal relationship. Our sample is 40 Indonesian banks listed on the Indonesian Stock Exchange for the years 2013-2016 with 160 observations as panel data. Based on panel data regression test, our results demonstrate that account receivables-related RPTs have a positive effect on banks' profitability and its market performance (Tobin's Q), but there are consequences of high operating costs and the risk of non-performing loans. Banks receive more funds from their related parties (account payables-related RPTs), banks exhibit higher capital capability and lower market performance. Further, the political connection index in banks significantly affect banks' capability, liquidity, efficiency, and market value through RPTs. This result indicates that political connection strengthens the effects of RPTs on banks' performance. Although this study has limited information in determining political connections and has not considered macroeconomic conditions, these findings imply that political connection plays an important role in banks' performance in Indonesia.
Keywords: G21; L25; M41; 650; related party transactions; political connection; firm performance; market performance; banks; Indonesia